Pulse plated Sn-Cu solder coatings from stannate bath - Sharma, Ashutosh; Ahn, Byungmin (Soldering and Surface Mount Technology, 2020)
Purpose: The purpose of this paper is to investigate the influence of pulse plating current density on the morphology and solderability of Pb-free Sn-Cu solder coatings prepared from alkaline stannate baths. Design/methodology/approach: Sn-Cu solder coatings were produced from a plating solution containing sodium stannate, copper stannate, sodium hydroxide and sorbitol additive on copper substrates. The pulse plating experiments were conducted in galvanostatic mode. The plating current density was varied from 5 to 25 mA/cm2, and the morphology of the coatings was studied. The solderability of the coatings was assessed by spread ratio measurement after reflowing the solder coatings at 250°C. Findings: The composition control of eutectic solders is always a challenge in plating. The findings show that Sn-Cu coatings prepared by pulse plating are composed of tetragonal ß-Sn structure and Cu6Sn5 compounds irrespective of bath composition and conditions. The final coatings were very dense and smooth with nodular morphology. It was shown that a eutectic composition can be achieved if we apply a current density of ∼15-20 mA/cm2. The solderability studies suggest that solder coatings plated at and beyond 15 mA/cm2 are more suitable for solder finish applications. Originality/value: The work presents key issues in pulse electroplating of Sn-Cu solder coatings from an alkaline bath. Possible strategies to control the eutectic Sn-Cu composition by plating process are recommended.
Keywords: Composition control; Design/methodology/approach; Eutectic composition; Galvanostatic measurement; Galvanostatic mode; Pulse electrodeposition; Pulse electroplating; Pulse plating; Electrodeposition; Galvanostatic measurements; Morphology; Morphology; Nucleation; Pulse electrodeposition; Pulse plating; Sn-Cu; Tin